Security policies in the Maghreb from the perspective of offensive realism - Fuente Cobo, Ignacio (Journal of the Spanish Institute for Strategic Studies, 2019)
The Maghreb is a regional system in which two states, Morocco and Algeria, potentially dominant because of their geographical size, population, size of their economy, military power and ability to influence, compete for a position of regional leadership. The hegemonic ambition in the regional context presides over the security policies of both states, which makes them tend to exaggerate the advantages of adopting expansive policies ignoring that, with this, they pose to their adversary a security dilemma aggravated by the problem of perceptions . Although the Maghreb constitutes a balanced bipolar security system and, therefore, little susceptible to military confrontation, the lack of information about the intentions of the other party feeds the regional competition and increases the possibilities of conflict
Keywords: Maghreb; Morocco; Algeria; Sahara; System; Dilemma; Security; Competition; Leadership; Confrontation